2015
DOI: 10.15414/jmbfs.2015.4.special2.98-100
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Turkey Spermatozoza Motility Parameters After Addition of Copper Sulphate in Vitro

Abstract: Copper as essential trace element is obligatory in many biological processes. Nevertheless higher concentrations of this metal are highly toxic for organisms at different levels and of course for spermatozoa. The aim of present work was to examine impact of copper sulphate on turkey spermatozoa motility parameters (line Big 6) during in vitro incubation at 41°C. Four concentration of CuSO4: M1 – 6.25 μg.ml-1; M2 – 12.5 μg.ml-1; M3 – 25.0 μg.ml-1; M4 – 50.0 μg.ml-1 were investigated. The motility parameters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Our results corroborate the findings of previous studies, reporting reductions in sperm motility and sperm velocity parameters after exposure to Cd or Cu in humans (Mukhopadhyay et al, 2010), rabbit (Roychoudhury & Massanyi, 2008), turkey (Slanina, Miškeje, Petrovičová, Lukáč, & Massányi, 2015), common carp (Chyb, Sokolowska-Mikolajczyk, Kime, Socha, & Epler, 2001) and African catfish (Kime, Ebrahimi, Nysten, Roelants, & Ollevier, 1996). Mukhopadhyay et al (2010) found a significant decline in VCL and STR in a tobacco-exposed group, whereas a heavy metal-exposed group had a significant reduced VCL and ALH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results corroborate the findings of previous studies, reporting reductions in sperm motility and sperm velocity parameters after exposure to Cd or Cu in humans (Mukhopadhyay et al, 2010), rabbit (Roychoudhury & Massanyi, 2008), turkey (Slanina, Miškeje, Petrovičová, Lukáč, & Massányi, 2015), common carp (Chyb, Sokolowska-Mikolajczyk, Kime, Socha, & Epler, 2001) and African catfish (Kime, Ebrahimi, Nysten, Roelants, & Ollevier, 1996). Mukhopadhyay et al (2010) found a significant decline in VCL and STR in a tobacco-exposed group, whereas a heavy metal-exposed group had a significant reduced VCL and ALH.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, this almost instant effect of CdCl 2 can be explained by the fact that Cd is highly toxic for mammalian cells (Telišman et al, 2000). Copper on the other hand occurs naturally, is an essential trace element and plays a vital part of several enzymes, such as ferroxidases, cytochrome c oxidase and superoxide dismutase (Slanina et al, 2015;Van Niekerk & Van Niekerk, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Motility was assessed at six time intervals: 0, 1, 2, 3, 4, and 5 h after spermatozoa collection and experiments were realized in six repetitions. The samples were evaluated doi: 10.17221/79/2017-CJAS using the CASA system (Computer Assisted Semen Analyser) with the Sperm Vision ® program (Minitube, Germany) equipped with a microscope Olympus BX 51 (Olympus Corp., Japan) to assess the spermatozoa motility (Massanyi et al 2008;Krockova et al 2012;Slanina et al 2015a). Each sample (10 μl) was placed into Makler Counting Chamber ® (depth 10 μm) (Sefi Medical Instruments Ltd., Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Hardneck et al [33] also found a significant negative effect on sperm motility at the highest concentrations of these two metals (250 µg/mL and 500 µg/mL). In turkey spermatozoa, it was reported that after 30 min of exposure, CuSO 4 (12.5 µg/mL to 50 µg/mL) significantly lowered the percentage total and progressive motility, as well as the values for VCL, ALH, and BCF [63].…”
Section: The Effect Of Heavy Metals On Sperm Motilitymentioning
confidence: 97%